Boganmeldelser - Gorm Toftegaard Nielsen; Jens Peter Christensen; Britta Kyvsgaard; Anne Palonen; Ida Koch; Henrik Tham; Pekka Viljanen; Vagn Greve (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews